Meritocracy in Village Government: Implementation of Village Apparatus Recruitment in Tuban Regency - Denny Iswanto; Durratun Nashihah; Ringga Ananta Putra (Institut Pemerintahan Dalam Negeri, 2026)
The implementation of meritocracy in village government is a crucial issue in realizing professional, transparent, and accountable village governance. In Tuban Regency, the simultaneous recruitment of village officials was implemented as an effort to standardize the selection process and minimize nepotism, political intervention, and subjective considerations in filling village official positions. However, the implementation of meritocratic principles in the recruitment process still requires further study. This study aims to analyze the implementation of meritocracy in the simultaneous recruitment of village officials in Tuban Regency and identify various obstacles encountered during the implementation process. This study used a qualitative approach with secondary data analysis methods. Data were obtained through a review of various documents, including laws and regulations, local government policies, recruitment implementation reports, legal decisions, media coverage, and relevant scientific literature. Data were analyzed using content analysis techniques through the stages of data reduction, data presentation, interpretation, and drawing conclusions. The results show that the simultaneous recruitment system has contributed to improved administrative standardization, transparency of the selection process, and more equal opportunities for participants. However, the implementation of meritocracy has not been optimal due to various obstacles, such as weak oversight mechanisms, indications of local political intervention, the use of conventional selection systems that are vulnerable to fraudulent practices, limited access to information, and low public trust in the neutrality of the selection process. This study concludes that the simultaneous recruitment of village officials in Tuban Regency is a positive initial step in realizing meritocratic-based village governance. However, strengthening the oversight system, increasing transparency, utilizing information technology in the selection process, and strengthening institutional capacity are still needed for the principles of meritocracy to be implemented more effectively and sustainably.